Vom kleinen Maulwurf, der wissen wollte, wer ihm auf den Kopf gemacht hat - Holzwarth, Werner,Erlbruch, Wolf (Hammer, 1998)
When Little Mole tries to find out who pooped on his head the other animals show him how they poop in order to prove their innocence.
Keywords: Defecation; Moles (Animals); Säugetiere; Kot; Tiere; Vergeltung; Maulwurf; Rache; Bilderbuch; Schadenermittlung; Körpergröße